2016
DOI: 10.1111/cmi.12691
|View full text |Cite
|
Sign up to set email alerts
|

TheBurkholderia cenocepaciapeptidoglycan-associated lipoprotein is involved in epithelial cell attachment and elicitation of inflammation

Abstract: The Burkholderia cepacia complex (Bcc) is a group of Gram-negative opportunistic pathogens causing infections in people with cystic fibrosis (CF). Bcc is highly antibiotic resistant, making conventional antibiotic treatment problematic. The identification of novel targets for anti-virulence therapies should improve therapeutic options for infected CF patients. We previously identified that the peptidoglycan-associated lipoprotein (Pal) was immunogenic in Bcc infected CF patients; however, its role in Bcc patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
1
28
2
Order By: Relevance
“…Although Burkholderia has been previously demonstrated to be a member of vaginal communities, the prevalence has been underappreciated, and its role in the community is unclear. It should be noted that Burkholderia is intrinsically resistant to clinically relevant antibiotics, which might confer a positive effect on the subversion of immune functions and the elicitation of inflammation, thus potentially facilitating the occurrence of SIL.…”
Section: Discussionmentioning
confidence: 99%
“…Although Burkholderia has been previously demonstrated to be a member of vaginal communities, the prevalence has been underappreciated, and its role in the community is unclear. It should be noted that Burkholderia is intrinsically resistant to clinically relevant antibiotics, which might confer a positive effect on the subversion of immune functions and the elicitation of inflammation, thus potentially facilitating the occurrence of SIL.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some examples of the strictly architecture-related role of PGN (i.e., elements that physically build the static PGN structure) can be found, and they are displayed in Table 1. For instance, the disruption of the PGN-associated lipoprotein (Pal) of Burkholderia cenocepacia (belonging to the BCC) has recently been linked to a major impairment in the virulence of this species in the Galleria mellonella larva infection model, together with a dampened capacity for host cell attachment and a weaker elicitation of inflammatory cytokine secretion (35). In a similar context, some papers have related the defects in yersinia Braun's lipoprotein to an important virulence impairment in murine models of infection, which suggested that the studied knockout (KO) mutants are potential vaccine candidates for bubonic and pneumonic plague (36)(37)(38).…”
Section: Dealing With Cell Wall Structure: Peptidoglycan-associated Lmentioning
confidence: 99%
“…remarkably different. The OmpA-like domain of PAL, on the other hand, is monomeric in -14 -solution and in the crystal structure [36]. Thus, it appears that PG-binding domains of proteins involved in ion translocation across the IM, i.e.…”
Section: Discussionmentioning
confidence: 92%